Russia: supporting non-democratic tendencies in the post-soviet space? - Antje Kästner (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Over the last decade, Russia has not only adopted a more authoritarian form of government, but has also become more active in the former USSR. Russia's growing engagement in its “near abroad” has been paralleled by the rise of illiberal regimes in the region, a development precipitated by active Russian policy action constraining the rise of Western democracy and reinforced by interests shared by the various governments. To react effectively to these trends, the governments of established democracies need to adjust their political strategies by integrating Russia into the international aid architecture, by reflecting on the comparative advantages they have over Russia in terms of development tools and by conducting an active but determined dialogue.
Keywords: 330